On reflection - Kornblith, Hilary (Oxford : Oxford University Press, 2012)
An account of mental reflection and its importance for knowledge, reasoning, freedom, and normativity. It argues that reflection cannot solve the philosophical problems it has been thought to, and offers a more realistic, demystified view of its nature which draws on dual process approaches to cognition.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Reflection (Philosophy); Knowledge, Theory of